Chemical Composition and Antioxidant Activity of Essential Oil of Leaves of Pistacia atlantica Desf. from Algeria - Gourine, Nadhir; Yousfi, Mohamed; Nadjemi, Boubakeur; Bombarda, Isabelle (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation of leaves of Pistacia atlantica at a yield of 0.13 % (v/w) were analyzed by GC/MS. Thirty one compound was identified representing 89.46 % of the total essential oil. The main components were β-pinene (19.08 %), α-terpineol (12.82 %), bicyclogermacrene (8.15 %) and spathulenol (9.45 %). The antioxidant activity of the oil, was evaluated in vitro using two different assays: DPPH• (2,2-di-phenyl-1-picrilpydrazyl) free radical-scavenging and FRAP (ferric reducing antioxidant power). The result of the DPPH assay gives an IC50 value of 9.61 ± 0.7 mg/mL. The FRAP antioxidant activity test of the oil was expressed using two standards reference antioxidants (ascorbic acid and butylated-hydroxyanisole). The antioxidant expressed as butylated-hydroxyanisol equivalent antioxidant capacity (BEAC) has a value of 8.73 ± 0.3 mM which means that the oil is much more active than butylated-hydroxyanisole. While the ascorbic-acid equivalent antioxidant capacity (AEAC), has a value of 54.77 ± 1.14 μM.